The NIMA-like kinase Nek2 is a key switch balancing cilia biogenesis and resorption in the development of left-right asymmetry - Endicott, S. Joseph (Development, 2015)
Vertebrate left-right (LR) asymmetry originates at a transient left-right organizer (LRO), a ciliated structure where cilia play a crucial role in breaking symmetry. However, much remains unknown about the choreography of cilia biogenesis and resorption at this organ. We recently identified a mutation affecting NEK2, a member of the NIMA-like serine-threonine kinase family, in a patient with congenital heart disease associated with abnormal LR development. Here, we report how Nek2 acts through cilia to influence LR patterning. Both overexpression and knockdown of nek2 in Xenopus result in abnormal LR development and reduction of LRO cilia count and motility, phenotypes that are modified by interaction with the Hippo signaling pathway. nek2 knockdown leads to a centriole defect at the LRO, consistent with the known role of Nek2 in centriole separation. Nek2 overexpression results in premature ciliary resorption in cultured cells dependent on function of the tubulin deacetylase Hdac6. Finally, we provide evidence that the known interaction between Nek2 and Nup98, a nucleoporin that localizes to the ciliary base, is important for regulating cilium resorption. Together, these data show that Nek2 is a switch balancing ciliogenesis and resorption in the development of LR asymmetry.